Efficacy of Bio-active Varnish Application on Microleakage of Class II Composite Resin Restorations: An in vitro Study - Bagu, Sindhuja V; Sajjan, Girija S; Varma, K Madhu; Bondada, Manisha; Ponnada, Naveena; Ketavathu, Durga Prasad Naik (International Journal of Dental Materials, 2025)
Background: Microleakage at the Cavo surface margins of Class II composite restorations remain a significant challenge, contributing to postoperative sensitivity, secondary caries, and restoration failure. Conventional composite resins undergo polymerisation shrinkage, resulting in marginal gaps and compromised seal integrity. To address these limitations, bioactive materials that can form chemical bonds with tooth structure and release therapeutic ions are being explored. Bioactive calcium phosphate-based fluoride varnishes offer potential in improving the marginal seal by reducing microleakage.Aim: To evaluate the efficacy of bio-active varnish application on microleakage at the Cavo surface margins of restorations.Materials and methods: Twenty extracted human maxillary premolars were divided into two groups (n = 10 each). Box-only cavities were prepared in 20 samples and restored with preheated bulk-fill composite. The samples in the control group (n = 10) were left untreated, without the application of varnish. Whereas, in the test group, the cavo surface margins of the restorations (n = 10) were sealed with MI varnish. All samples were then immersed in a 0.5% basic fuchsin dye for 24 hours. They were sectioned mesiodistally and observed under a stereomicroscope at 20x for dye penetration. Cervical microleakage was recorded following the ISO score system. The data were analysed statistically with a chi-square test.Results: No significant difference in microleakage was observed in the control and test groups. However, the cavo surface margins of the test group samples showed improved performance, with only 10% of the samples demonstrating score-1 leakage.Conclusion: No significant difference in microleakage was observed in the control and test groups. However, the cavo surface margins of the test group samples showed improved performance, with only 10% of the samples demonstrating score-1 leakage.